The Exclusive Rights of Licensees in Parallel Import Practices - Edbert Seligshan Horman (Yuridika, 2021)
Parallel imports are one of the most interesting and unique phenomena of international trade. On one hand, it applies competition law, while on the other, trademark law and the customs law also apply in this activity. Parallel imports occur when genuine goods are imported in parallel (concurrently) to goods imported by a licensee. These parallel imports are then sold at a cheaper price than that of the  goods of the licensee. This parallel import activity is inconsistent with the exclusive rights that the licensee receives under the licensing agreement it makes with the owner of the trademark. This exclusive right is essentially monopolistic, entitling the licensee to prevent all parties with the commercial intention of selling the same or similar goods as their own. However, the right to monopoly is limited for the sake of a fair competition. The licensee can sue to get compensation in parallel importation base on unjust enrichment principle. Moreover, parallel importation can be inhabited by enforcing procedural and administration regarding import of goods such as, Indonesian national standard and label in bahasa